MEMPERSIAPKAN KOMPETENSI KEPRIBADIAN CALON KONSELOR DI ERA MASYARAKAT EKONOMI ASEAN (MEA) - Ulya Makhmudah (Universitas Sebelas Maret, 2017)
The end product of this research is a measuring instrument to reveal the mastery of personal competence counselor. The measuring instrument was developed based on government regulation No. 27 Year 2008 concerning the standard of competence counselor. Through the development of this measure is expected to be obtained by standard that can be used to determine the extent of the values of a strong personality of a counselor has integrated within student guidance and counseling. This measure is also expected to be entered in the improvement of the curriculum especially for integrating personal competence counselors in each subject. Curriculum and subject that have been repaired, can support the maturity of personal competence counselor preparation to face the Asean Economic Community (AEC). The method used in this research is the research and development methods.